Powertrain Warm-Up Optimization Involving Simplified Split Cooling with Integrated Exhaust Heat Recovery and Reuse - Osman, A. (SAE International, 2018)
The test results published earlier have proven that the previously proposed engine cooling circuit when combined with exhaust heat recovery and reuse could expedite the warm-up process after cold start and has improved the fuel economy by up to 4. With the evolution of the earlier concept, the study discussed in this paper explores further improvements to the cooling circuit to expedite the warm-up process. In particular, with some changes to the cooling circuit, the heat recovered from the exhaust gas is reusable right away to heat up the heat exchangers for engine oil, CVT oil and cabin heater. Next, the thermostat opening temperature and leakage rate can also be optimized to prolong the heat recirculation and preservation periods. Finally, the coolant flow rate across the heat recovery unit can also be varied as a function of time right after the cold-start. These additional measures although capable of improving the warm-up process come with limitations. For example, prolonged throttling of the coolant flow across the heat recovery unit can be risky in terms of component overheating and coolant boiling. Some coolant boiling although tolerable to certain extent in many modern engines may cause prolonged coolant flow interruption across the heat recovery unit. In addition to that, the throttling of coolant flow although favorable in conserving heat in the cylinder head, it hinders the heat transfers to CVT and engine oils. In the paper, the warm-up periods when the parameters changed are evaluated during idle, NEDC and internally developed actual driving cycle. The warm-up periods of the proposed improvements are later compared with the warm-up periods of Baseline cooling circuit and the previously proposed cooling circuit. Â© 2018 SAE International. All Rights Reserved.